Simulation and Sensitivity Analysis of Molybdenum Disulfide Nanoparticle Production Using Aspen Plus - Mouad Hachhach; Hanane Akram; Mounir Hanafi; Ouafae Achak; Tarik Chafik (International Journal of Chemical Engineering)
The sensitivity analysis of molybdenum disulfide nanoparticles synthesis process is studied using Aspen Plus with the aim of investigating the effect of reactants’ amounts on the production of molybdenum disulfide nanoparticles. The adopted approach consists in simulating the synthesis process based on experimental data, obtained at laboratory scale followed by sensitivity analysis with respect to the following precursors: ammonium heptamolybdate, elemental sulfur, and hydrazine used as a reducing agent. The sensitivity analysis revealed that the precursors have more significant impact on the obtained amount of molybdenum disulfide compared to hydrazine. The obtained result showed that the approach adopted in the study might be of interest for further investigation of the process design and scaling-up.